(untitled) (Szociológiai Szemle, 2024)
The paper offers a comparative analysis of a new (to Central-Eastern Europe) phenomenon: national level institutionalized tripartism (neo-corporatism). It describes tripartism and its functioning in: public policy formation; the prevention and settlement of social conflicts; and in the formation of new relations to labour and employment. It also attempts to determine which political and economic considerations have contributed to the birth and survival of tripartite structures, and which political and economic weaknesses make them vulnerable. The paper concentrates on Hungary, Bulgaria, Poland, the Czech Republic, and Slovakia.